Assessment of leaf properties on mustard varieties exhibiting resistance to aphid and sawfly infestation - Moshfiqur Rahman; Md Ruhul Amin; Md. Mamunur Rahman; Mansura Afroz; Md. Raihan Talukder; Antara Samiha; Ariful Islam; Md. Shamim Hossain (Penerbit Universiti Kebangsaan Malaysia, 2023)
The current study was conducted in the experimental field of the Department of Entomology, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh from November 2019 to March 2020 to explore host plant resistance of seven mustard varieties, namely BARI Sarisha-11, BARI Sarisha-12, BARI Sarisha-13, BARI Sarisha-14, BARI Sarisha-15, BARI Sarisha-16, and BARI Sarisha-17 against sawfly and aphid based on leaf biochemical parameters. Chlorophyll a, chlorophyll b, reducing sugar, protein, and proline of leaf showed significant variations but Soil Plant Analysis Development (SPAD) value showed no statistical variation among the varieties. The mean infestation rate of sawfly was the highest in BARI Sarisha-12 (4.2±2.2%) and the lowest was in BARI Sarisha-13 (0.0±0.0%). The infestation of aphid was also the lowest in BARI Sarisha-13 (15.2±0.7%), but the highest was in BARI Sarisha-14 (24.9±1.5%). The correlation matrix showed that the estimated biochemical contents of leaf except proline showed positive influence on the infestation of both sawfly and aphid, but only reducing sugar, protein and proline showed significant results. Among the studied varieties, BARI Sarisha-13 showed comparatively lower level of abundance and infestation of both sawfly and aphid